2007
DOI: 10.1097/01.brs.0000255076.45825.1e
|View full text |Cite
|
Sign up to set email alerts
|

The Management and Functional Outcome of Isolated Burst Fractures of the Fifth Lumbar Vertebra

Abstract: In the largest series to date of isolated burst fractures of L5, we strongly advocate the nonoperative management of these injuries, particularly in cases of moderate bony deformity, minimal canal compromise, and no neurologic deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 13 publications
1
37
1
1
Order By: Relevance
“…9) Conservative management was proposed in patients with isolated burst fractures of the L5 vertebra without neurological damage and satisfactory clinical outcome with very good pain status was reported. 5,6) In contrast to the results of Mick et al 14) described a significant loss of height in the anterior column in five patients treated non-operatively, whereas in six fractures that underwent posterior stabilization, an increase of height in the anterior column was noted. They propose conservative management in young patients with minimal canal compromise.…”
Section: Discussioncontrasting
confidence: 54%
“…9) Conservative management was proposed in patients with isolated burst fractures of the L5 vertebra without neurological damage and satisfactory clinical outcome with very good pain status was reported. 5,6) In contrast to the results of Mick et al 14) described a significant loss of height in the anterior column in five patients treated non-operatively, whereas in six fractures that underwent posterior stabilization, an increase of height in the anterior column was noted. They propose conservative management in young patients with minimal canal compromise.…”
Section: Discussioncontrasting
confidence: 54%
“…When intact pedicles were found at L5, short transpedicular screws can be used at the aforementioned level. We always aimed at lordotic contouring of the instrumentation, as many authors [12,20] reported better results when spino-pelvic profile was unmodified. Rod contouring, together with definitive fixation performed with extended hips and knees, seems to help in preventing kyphosis and sacral verticalization.…”
Section: Discussionmentioning
confidence: 99%
“…Very little has been written [2][3][4][5] and some of the published papers include either L3 and L4 fractures [6][7][8] or patients with no neurological impairment undergoing conservative treatment [9][10][11][12]. Burst or compression fractures type A in Magerl classification [13] are more frequently found, whilst flexiondistraction fractures (type B) and fractures with rotation/ dislocation (type C) are uncommon [14].…”
Section: Introductionmentioning
confidence: 99%
“…Burst fractures of the low lumbar spine constitute roughly 1% of all lumbar fractures, and frequently caused by high-energy trauma [1][2][3]. The lumbosacral spine possess a critical role in axial weightbearing of the spine [2].…”
Section: Introductionmentioning
confidence: 99%
“…The lumbosacral spine possess a critical role in axial weightbearing of the spine [2]. This segment of the spine has unique anatomic and biomechanical characteristics, including its location below the pelvic brim and the apex of the lumbar lordosis in conjunction with the stabilizing effect of the iliolumbar ligaments that protect this region from traumatic injury [2,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%